Mimicry and the Native American ‘Other’ - Tia Byer (Forum, 2019)
This paper will address the sustained feeling of separation and delineation in Zitkála-Šá’s literature and Homi Bhabha’s postcolonial theorization, which discuss the difficulties of speech and language in a postcolonial context. I analyse the survival of Native American Culture during late nineteenth-century assimilation, in Zitkála-Šá’s ‘The School Days of an Indian Girl’, and evaluate Homi Bhabha’s ground-breaking research in employing colonial mimicry to usurp colonial power discourses. When former colonial subjects appropriate the colonizer’s language, psychological barriers such as perceived native cultural inferiority transpire. Adhering to an Anglo-American Education, Zitkála-Šá becomes victim to cultural shame and a consequent splitting-of-the self. Bhabha’s theory however, purports to provide a means of overcoming the barrier presented by cultural difference, by implying that imitation of a colonial language ensures camouflage-like protection for the colonial subject which in turn enables them to occupy a dual position in society that is both within their cultural heritage and the colonial environment of ‘civilization’. The extent, to which this is readily achievable, becomes contestable when read alongside Zitkála-Šá. I challenge the penetrable strivings of Bhabha’s theory, by revealing the flaws in his deconstructionist postcolonialism. My examination of power discourses in each text identifies cultural assimilation as an invisible barrier.